"Selections from political writings (1910-1920)/Selected and edited by Quintin Hoare, translated by John Mathews" - "Gramsci, Antonio" (London, 1977)
About the Book: Selections from Political Writings 1910-1920 This volume is the first of two containing a selection of Antonio Gramscis political writings from the time of his initial involvement in Italian politics to his imprisonment by Mussolini in 1926. This selection culminates in the Red Years of 1919-20, and also features texts by Bordiga and Tasca from their debates with Gramsci. It traces Gramscis development as a revolutionary socialist during the First World War, die impact on his thought of the Russian Revolution and his involvement in the general strike and factory occupations of 1920. Also included are his reactions to the emerging fascist movement and contributions to the early stages of die debate about the establishment of the Communist Party of Italy.
Keywords: Political science